2013
DOI: 10.5049/ebp.2013.11.2.53
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hypernatremia by Excessive Bamboo Salt Ingestion in Healthy Young Woman

Abstract: Severe hypernatremia is an important electrolyte disorder that has serious effects. The patient had no medical history. A. 20-year-old ingested bamboo salt for digestion and weight reduction according to the folk remedies posted on an internet website. She presented with vomiting and diarrhea over ten times per day. Her initial serum sodium concentration was 174mEq/L. Her symptoms improved rapidly with hypotonic saline infusion. She recovered completely without any sequelae in three days. Severe hypernatremia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…If these losses are not replaced with free water intake, or if they are accelerated by conditions such as fever, burns, or exercise, hypernatremia may result. Hypernatremia can also occur via secretory losses of hyponatric fluid in either the upper or lower gastrointestinal tract, after large-volume salt ingestion or absorption (salt poisoning), 10 and in the setting of osmotic diuresis caused by glucose, urea, or mannitol. 11 In all of these cases, hypernatremia is usually transitory and alleviated over time by increased thirst and free water retention, which is a direct result of AVP secretion in response to increased plasma osmolality.…”
Section: Discussionmentioning
confidence: 99%
“…If these losses are not replaced with free water intake, or if they are accelerated by conditions such as fever, burns, or exercise, hypernatremia may result. Hypernatremia can also occur via secretory losses of hyponatric fluid in either the upper or lower gastrointestinal tract, after large-volume salt ingestion or absorption (salt poisoning), 10 and in the setting of osmotic diuresis caused by glucose, urea, or mannitol. 11 In all of these cases, hypernatremia is usually transitory and alleviated over time by increased thirst and free water retention, which is a direct result of AVP secretion in response to increased plasma osmolality.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports describe cases with acute hypernatremia who had a favorable outcome following treatment with the slow sodium correction rate. 2,4,6,7 In light of these findings, aggressive therapy should not be considered for all cases presenting with salt intoxication. In those cases where organic osmolytes have already started accumulating in the brain cells to adapt to hypertonic stress, a more cautious procedure should be selected to correct hypernatremia, that is, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A LTHOUGH HYPERNATREMIA USUALLY results from hypovolemia, underlying diseases, and iatrogenic results, previous studies have also reported several cases of salt poisoning. [1][2][3][4][5][6][7][8][9] Nevertheless, standard care procedures for salt poisoning have not yet been established due to a limited number of such cases. Aggressive therapy has been attempted in several cases in order to prevent mortality; however, more studies on salt poisoning are necessary.…”
mentioning
confidence: 99%
“…It is believed that the trace elements in the mud and bamboo make this form of salt healthier. 2 Bamboo salt has been added to toothpaste and according to the manufacturer this toothpaste can prevent cavities, reduce plaque and gingivitis, soothe sensitive teeth, fight bad breath, whiten teeth, strengthen tooth enamel, prevent receding gum line and decrease mineral loss. Numerous bamboo salt toothpastes are available in Japan, Hong Kong, Korea and worldwide through the Internet (Fig.…”
Section: Oral Health Bamboo Saltmentioning
confidence: 99%
“…1 Therefore, a new class of platelet antagonists targeting thrombinmediated platelet activation via proteaseactivated receptors (PAR) have been developed to address these issues. 2 The first drug in this group, vorapaxar, a PAR1 antagonist, has just been approved by the FDA 3 for the reduction of thrombotic cardiovascular events in patients with a history of myocardial infarct and peripheral arterial disease but not in those with a history of stroke or transient ischaemic attack (due to the increased risk of intracranial haemorrhage observed in clinical trials in these two groups). [4][5][6] Vorapaxar is rapidly absorbed after oral administration with onset of activity at two hours.…”
Section: Pharmacology a New Bleeding Issuementioning
confidence: 99%